2020
DOI: 10.1155/2020/3936242
|View full text |Cite
|
Sign up to set email alerts
|

Neimark–Sacker Bifurcation of a Two-Dimensional Discrete-Time Chemical Model

Abstract: In this paper, the local dynamics and Neimark–Sacker bifurcation of a two-dimensional glycolytic oscillator model in the interior of ℝ+2 are explored. It is investigated that for all α and β, the model has a unique equilibrium point: Pxy+α/β+α2,α. Further about Pxy+α/β+α2,α, local dynamics and the existence of bifurcation are explored. It is investigated about Pxy+α/β+α2,α that the glycolytic oscillator model undergoes no bifurcation except the Neimark–Sacker bifurcation. Some simulations are given to verify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Lemma 2.2. [15,17,22,34] Assume F (λ) = λ 2 + Bλ + C, where B and C are two real constants and let F (1) > 0. Suppose λ 1 and λ 2 are two roots of F (λ) = 0.…”
Section: Stability Analysis and Fixed Points Of The Systemmentioning
confidence: 99%
“…Lemma 2.2. [15,17,22,34] Assume F (λ) = λ 2 + Bλ + C, where B and C are two real constants and let F (1) > 0. Suppose λ 1 and λ 2 are two roots of F (λ) = 0.…”
Section: Stability Analysis and Fixed Points Of The Systemmentioning
confidence: 99%
“…The results of their study show that the system exhibits abundant dynamical behaviors and the chemical reaction in the reactor will be in balance in the end under certain conditions. Khan [22], in his paper, studied the local dynamics and Neimark-Sacker bifurcation of a two-dimensional glycolytic oscillator model. It was found that the model has a unique equilibrium point for all α and β.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we calculate the critical coefficients of each bifurcation. The two-dimensional discrete-time chemical model under consideration is given as follows [22]…”
Section: Introductionmentioning
confidence: 99%
“…See [12] and references therein for examples of fitting parameters of models. Some most recent applications of Neimark-Sacker bifurcation for differential equations can be found in [13] and for difference equations in [14]. Some global asymptotic results for second order difference equations related to the results from [10], which will be used in the present paper, can be found in [15].…”
Section: Introductionmentioning
confidence: 99%